A nonsense mutation in the PRKG2 gene in dalmatian dogs with chondrodysplasia - Suvi Mäkeläinen; Stina Ekman; Marjo K. Hytönen; Hannes Lohi; Kaisa Kyöstilä; Thomas Simon; Göran Andersson; Åke Hedhammar; Kerstin Hansson; Tomas F. Bergström (PLoS ONE, 2025)
Skeletal dysplasias encompass a diverse group of genetic disorders characterized by short stature and dwarfism. In humans, 771 types of skeletal dysplasia have been documented. Similar forms of these disorders have also been observed in dogs. The first cases of documented skeletal dysplasia in Dalmatian dogs were reported in the early 1980s, with additional affected dogs observed in subsequent years. Careful radiological and histopathological examinations at the time revealed severe limb deformities, including shortened radii and ulnae, irregular growth plates and disrupted endochondral ossification. In this study, we applied whole-genome sequencing on samples collected in 1992 and identified a genetic variant in the PRKG2 gene, introducing a premature stop codon (XM_038582312: c.1601T > G, p.L534X). Genetic variants in PRKG2 have previously been implicated in human acromesomelic dysplasia, a disorder affecting limb growth in young children. The PRKG2 -encoded protein plays a crucial role in endochondral ossification, and if translated, the identified nonsense variant would result in a truncated protein lacking most of the catalytic domain. Extended screening of the genetic variant revealed its continued segregation in the current Dalmatian population. Furthermore, three recent cases of dwarfism in Dalmatians were found to be homozygous for the identified PRKG2 nonsense variant. These findings provide compelling evidence for the role of PRKG2 in Dalmatian dwarfism, resolving a decades-old genetic mystery in the breed.